DRUG DELIVERY ENHANCEMENT STRATEGIES THROUGH CORNEA: A REVIEW - RATHORE, MAHENDRA SINGH (Asian Journal of Pharmaceutics (AJP), 2016)
Eye is the specialized organ for photorecept ion that poses unique challenges for drug delivery. Eye diseases can be t reated with systemic, int raocular and/ or topical administ rat ion of drugs. The review highlights the challenges in ocular drug delivery through various routes with emphasis on topical route. The corneal transport process for different drugs is also touched. Different approaches for drug delivery enhancement through cornea are discussed with special at tent ion on chemical modificat ion (prodrug) approach. Nutrient transporter targeted prodrug design approach are discussed with special reference to amino acid prodrug design approach for enhanced drug delivery